Activation of host translational control pathways by a viral developmental switch. - Carolina Arias (Public Library of Science (PLoS), 2009)
In response to numerous signals, latent herpesvirus genomes abruptly switch their developmental program, aborting stable host-cell colonization in favor of productive viral replication that ultimately destroys the cell. To achieve a rapid gene expression transition, newly minted capped, polyadenylated viral mRNAs must engage and reprogram the cellular translational apparatus. While transcriptional responses of viral genomes undergoing lytic reactivation have been amply documented, roles for cellular translational control pathways in enabling the latent-lytic switch have not been described. Using PEL-derived B-cells naturally infected with KSHV as a model, we define efficient reactivation conditions and demonstrate that reactivation substantially changes the protein synthesis profile. New polypeptide synthesis correlates with 4E-BP1 translational repressor inactivation, nuclear PABP accumulation, eIF4F assembly, and phosphorylation of the cap-binding protein eIF4E by Mnk1. Significantly, inhibiting Mnk1 reduces accumulation of the critical viral transactivator RTA through a post-transcriptional mechanism, limiting downstream lytic protein production, and impairs reactivation efficiency. Thus, herpesvirus reactivation from latency activates the host cap-dependent translation machinery, illustrating the importance of translational regulation in implementing new developmental instructions that drastically alter cell fate.